Suspected child sexual abuse and the role of the health care professional in diagnosis and treatment 1 - Finkel, Martin A. (Henry Stewart Talks, 2018)
Historical and developmental perspectives of recognizing and treating child sexual abuse, Definitions of child sexual abuse, The clinical presentation of child sexual victimization, Purpose of medical examination of potential sexual abuse victims